The Influence of Using Genre Based Instruction (GBI) in Writing Skill Exposition Text in Students SMPN 3 Pringgarata - Hendra Suryadi; Evi Safitri Yulandari (LP. Ma'arif Janggan Magetan, 2022)
This study was aimed at finding out the influence of genre-based instructional model in the teaching of writing skills viewed from students’ text exposition. This study employed a quasi-experimental research design. The samples consisted of two classes in which one class was treated by using genre-based instructional (GBI) model and the second class was subjected to the process-based instruction (PBI) model. The writing exposition text were functioned as research instruments to collect the data in both classes. The data were analyzed by using the multifactor analysis of variance (ANOVA). The research finding informed that the GBI model was more influence than the PB model I. It was proved with the value of Process-Based Instruction (56) was lower than Genre Based Instruction (69). It means that the used of Genre Based instructional model have influence in writing skills exposition text. The finding indicates that there is significant interaction between instructional being applied in the teaching of writing skill exposition text.